Determining the Relationship Between Maternal and Neonatal Vitamin D Serum Levels in Term Infants With and Without Sepsis - Mahbod Kaveh; Maryam Noory; Mohammad Kaji Yazdi; Shima Jeiroodi (Journal of Family and Reproductive Health)
Objective: To investigate the relationship between maternal and neonatal vitamin D serum levels in term infants with and without sepsis. Materials and methods: This is a case-control study with 320 participants which include , 80 mothers and babies with neonatal sepsis and 80 control mothers and babies without neonatal sepsis that included in  their quantitative vitamin D levels were compared with each other survey. Results: Demographic and clinical characteristics of infants (age at admission, gender) and mothers (age, education level) were recorded. Blood samples were taken to check serum vitamin D levels of these babies along with their mothers. Vitamin D levels were classified as deficiency less than 10 ng/ml, moderate deficiency 10-30 ng/ml, mild deficiency 20-30 ng/ml and normal 100-30 ng/ml.33 (41.3%) of the infants born in the neonatal sepsis group and 45 (56.3%) of the control infants were male. Using Fisher’s exact test, no significant difference was found between the two groups in terms of gender distribution, P=0.082. The median age of infants in the neonatal sepsis group was 5 (3-9) days and in the control group was 5 (4-6) days. The mean (age of mothers in the patient group was 29.6 (6.4) years and in the control group was 29.7 (5.6) years. The median range of maternal vitamin D levels in the neonatal sepsis group was 23.8 (15.0-30.0) and 28.6 (17.1-34.0) ng/ml in the control group. According to the Mann-Whitney U statistical test, the vitamin D level of mothers in the neonatal sepsis group was significantly lower than that of the group was the control (p=0.020). Conclusion: According to the result of the Mann-Whitney U test, the vitamin D level of mothers in the neonatal sepsis group was significantly lower than the control group (P=0.020). Mother’s vitamin D level maybe related to the incidence of neonatal sepsis.